1993
DOI: 10.1136/bmj.306.6870.102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two school smoking education programmes under normal classroom conditions.

Abstract: Objectives-To assess the effectiveness of two school based smoking education projects in delaying onset of smoking behaviour and in improving health knowledge, beliefs, and values.Design-Cluster randomised controlled trial of two projects taught under normal classroom conditions. Schools were allocated to one of four groups to receive the family smoking education project (FSE); the smoking and me project (SAM); both projects in sequence (FSE/SAM); or no intervention at all.Setting-39 schools in Wales and Engla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(54 citation statements)
references
References 17 publications
1
48
0
5
Order By: Relevance
“…Un dato interesante es que no hubo diferencias entre fumadores y no fumadores conforme al grado de información recibida en la escuela sobre el tabaco y el daño a su salud. Existe, en este sentido, alguna evidencia de otros estudios de que el aumento de conocimientos impartidos en la escuela no provoca reducción en la tasa de fumadores 9,24,25 . Intimidar a los niños con hechos mórbidos probablemente sea ineficaz.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Un dato interesante es que no hubo diferencias entre fumadores y no fumadores conforme al grado de información recibida en la escuela sobre el tabaco y el daño a su salud. Existe, en este sentido, alguna evidencia de otros estudios de que el aumento de conocimientos impartidos en la escuela no provoca reducción en la tasa de fumadores 9,24,25 . Intimidar a los niños con hechos mórbidos probablemente sea ineficaz.…”
Section: Discussionunclassified
“…Como contraposición se observa el efecto ganador de las propagandas realizadas por las industrias tabacaleras 14,26 . Mientras que algunos programas han reportado cierto éxito en la prevención entre jóvenes 9,27-30 otros reflejan una pobre eficiencia 24,31,32 .…”
Section: Discussionunclassified
“…16 17 Gilchrist et al 17 found that, in an evaluation of a self control intervention, smoking rates in the intervention group-which received in-class sessions on factual information about smoking and health-were higher than in the control group. Finally, in an evaluation of two school based smoking education programmes in Wales, Nutbeam 18 reported that non-smoking youth exposed to the programmes were less likely to remain never smokers compared to non-smokers not exposed to the programme.…”
mentioning
confidence: 99%
“…Siden Horn gjennomførte sine studier, har det kommet mange undersøkelser av liknende type. Noen evalueringer har ikke påvist noen vesentlig virkning av slike tiltak (7,8), mens andre har gitt større grunn til optimisme. Det er utviklet nye begreper, modeller og teorier som gir oss holdepunkter for hva slags faktorer som er avgjørende for barn og unges røyke-vaner, og som gjør at vi kan forbedre intervensjonsmetodene (9,4).…”
Section: Innledningunclassified